Brassinazole resistant 1 (BZR1)-dependent brassinosteroid signalling pathway leads to ectopic activation of quiescent cell division and suppresses columella stem cell differentiation - Lee, Hak-Soo (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.